Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pendapatan Pelaku Usaha Mikro Dan Kecil di Kecamatan Mamuju - Mappigau, Ernawaty (LPPM Universitas Muhammadiyah Mamuju, 2023)
The purpose of this study is to analyze the factors of length of business, capital, and working hours simultaneously affecting the level of income of Micro and Small Business actors in Mamuju District and to analyze the factors of business length, capital, and working hours partially affecting the income level of Micro and Small Business actors. Small in Mamuju District. The type of data used in this study includes quantitative data and qualitative data. In this study, a 10% margin of error was used in determining the number of samples. The results of the calculation of the slovin formula above show that the number of samples in this study was 62. The data analysis method used was multiple linear regression analysis. In this study the analytical test tools used by the author are partial tests and simultaneous tests. Based on the partial multiple linear regression test, it shows that the length of business variable has the most dominant influence on the Income Level of Micro and Small Business Actors, Mamuju District, Mamuju Regency. From the results of the study it was found that length of work, capital and working hours jointly affect the Income Level of Micro and Small Business Actors in Mamuju District, Mamuju Regency.